CULTIVATING OF INDEPENDENCE, CRITICAL THINKING AND CIVIC SELF-CONSCIOUSNESS IN PROTECTION FROM MANIPULATIVE INFLUENCES - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2025)
The accelerated rise of the knowledge sector’s role and share guarantees both an upward trajectory of economic and social transformation and an increase in sovereignty and security. Today, the revival and further development of the sector requires an emphasis on the development, analysis, adaptation, and dissemination of knowledge